Profesionalisme Guru dalam Menumbuhkan Nilai Karakter Siswa Berbasis Nilai-Nilai Budaya 5S (Senyum, Sapa, Salam, Sopan, Santun) di SMK 1 Muhammadiyah Kasihan Bantul Yogyakarta - Yusutria; Sutarman (Universitas Muhammadiyah Prof Dr Hamka, 2021)
The cultivation of 5S culture in instilling religious character imbues the teachings of Islamic values. So that professional teachers help grow the character values